The Manchester Super Casino: Experience and Learning in a Cross-Sector Social Partnership - Reast, Jon (Journal of business ethics, 2010)
The management of cross-sector social partnerships (CSSPs) among government, business, and not-for-profit entities can be complex and difficult. This article considers the importance of organizational experience and learning for the successful development of CSSPs. By analyzing the Manchester Super Casino, this research emphasizes the significant benefits of prior experience with CSSPs that enable partners to learn and develop relationships, skills, and capabilities over time, which then have positive influences on future performance. The result is a refined learning model of the CSSP process that includes key variables for CSSP success. As such, these findings provide a template for managing complex CSSPs from the perspective of the different partner organizations.